Reducing Coating Defects by Implementing Auto Dripping System on The Finishing Machine - Octowinandi, Vivin; Firdaus, Fadli; Arifin, Muhammad; Maulidiah, Hana Mutialif; Iqbal, Muhammad (Journal of Applied Electrical Engineering, 2023)
Finishing Process is one of the most important processes in the manufacture of resistors, because it is the process of forming the resistor body by coating the resistor with a coating liquid. However, in this process there are still many cases of product defects, one of the main causes is the uncontrolled viscosity of the coating liquid causing the formation of body resistors is not good, or what is called Body deform and body thin defects. Auto Dripping is a useful tool for automatically dripping methanol liquid which aims to control the viscosity of the coating liquid in the finishing process. Because Auto Dripping is a tool that has just been implemented and does not yet have the right parameter settings, it is necessary to do trials to find the right parameters so that Auto Dripping functions properly. In Auto Dripping there are two settings that can be controlled, namely Stroke Speed and Stroke Length, these two settings affect the output of methanol liquid that comes out. In this study using SPC tools to analyze the parameters being tested, namely the Control Chart which is used to monitor the stability of a process and study process changes from time to time. then, in this study also used the Process Capability Analysis method. This method is very effective in viewing the performance of a process, is used to measure process capability by comparing its distribution with the distribution of specifications accurately and provides a clearer picture. After carrying out this project, the authors concluded that the implementation of the Auto Dripping set up parameter has proven to be quite influential in reducing the case of coating defects caused by uncontrolled viscosity, namely by maintaining the stability of the coating viscosity so that it can produce resistors that meet specifications. From the data above, the production of resistors has been running stably with a period of 5 weeks, with 100 resistor samples being measured. With an average value of 2.82 mm. As for the Cpk value after implementing the new parameter setup, which is 3.35, this is a high result and meets the standard, which is ≥1.5.